2018
DOI: 10.1111/imm.12997
|View full text |Cite
|
Sign up to set email alerts
|

γδ T cells modulate humoral immunity against Plasmodium berghei infection

Abstract: It is unclear whether γδ T cells are involved in humoral immunity against Plasmodium infection. Here, we show that B-cell-immunodeficient mice and γδ T-cell-deficient mice were incapable of protecting against Plasmodium berghei XAT parasites. γδ T-cell-deficient mice developed reduced levels of antigen-specific antibodies during the late phase of infection. The numbers of follicular helper T cells and germinal centre B cells in γδ T-cell-deficient mice were lower than in wild-type mice during the late phase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Interestingly, γδ T cell expression of CD16, which is known to mediate antibody-dependent cellular cytotoxicity (ADCC) in CMV infection ( 24 ) is increased in children in malaria-endemic regions ( 34 , 35 ), suggesting a potential role for γδ T cells in inciting antibody-mediated parasite killing (Figure 1 ). Finally, paralleling previous observations during influenza infection ( 98 ), recent work in the P. berghei mouse model demonstrated a role for γδ T cells in increasing levels of antigen-specific antibodies, Tfh cells, and germinal center B cells via expression of IL-21 and IFNγ early in infection ( 54 ). Altogether, evidence suggests that malaria-responsive γδ T cells are able to use diverse direct and indirect (via recruitment of monocytes, dendritic cells, and CD4+ cells) mechanisms to influence effector responses later in infection.…”
Section: γδ T Cell Roles In Stimulating Other Innate and Adaptive Immsupporting
confidence: 78%
See 1 more Smart Citation
“…Interestingly, γδ T cell expression of CD16, which is known to mediate antibody-dependent cellular cytotoxicity (ADCC) in CMV infection ( 24 ) is increased in children in malaria-endemic regions ( 34 , 35 ), suggesting a potential role for γδ T cells in inciting antibody-mediated parasite killing (Figure 1 ). Finally, paralleling previous observations during influenza infection ( 98 ), recent work in the P. berghei mouse model demonstrated a role for γδ T cells in increasing levels of antigen-specific antibodies, Tfh cells, and germinal center B cells via expression of IL-21 and IFNγ early in infection ( 54 ). Altogether, evidence suggests that malaria-responsive γδ T cells are able to use diverse direct and indirect (via recruitment of monocytes, dendritic cells, and CD4+ cells) mechanisms to influence effector responses later in infection.…”
Section: γδ T Cell Roles In Stimulating Other Innate and Adaptive Immsupporting
confidence: 78%
“…In addition, inflammation during recurrent malaria leads to suppression of functional memory B cells (MBC) ( 111 ) and expansion of “inferior” T follicular helper (Tfh) cells ( 112 , 113 ) and “atypical” MBC exhibiting impaired proliferation, cytokine production and antibody secretion ( 114 ). Considering the overlapping timing of immunoregulatory phenotypes developing in γδ T cells and adaptive cells, as well as evidence for γδ T cells impacting germinal center reactions in murine malaria ( 54 ) and Tfh differentiation during influenza ( 98 ), future research should examine the impact of altered γδ T cell function on expansion of MBC and Tfh subsets and interactions with other immune cells.…”
Section: Directions For Future Research and Application To Potential mentioning
confidence: 99%
“…Despite the tissue distribution and the omnipresence of IL-21 target cells in tissues in which protozoan and helminth parasites reside, the role of the IL-21/IL-21R signaling pathway in protection against and/or the promotion of inflammation during parasitic infections is not fully understood. In recent years, however, it has been observed that IL-21 is induced in the periphery and mucosal tissues of humans and mice after infection with some parasites (Stumhofer et al, 2013; Carpio et al, 2015; Perez-Mazliah et al, 2015; Cai et al, 2016; Ryg-Cornejo et al, 2016; Moretto et al, 2017; Inoue et al, 2018; Wikenheiser et al, 2018) (Table 1). However, the exact mechanisms by which this signaling pathway regulates host immunity during parasitic infections are still unclear.…”
Section: Il-21/il-21r Signaling Pathwaymentioning
confidence: 99%
“…IL-21 is expressed in several murine malaria models, including P. berghei (Ryg-Cornejo et al, 2016; Inoue et al, 2018), Plasmodium chabaudi (Perez-Mazliah et al, 2015; Sebina et al, 2017) and Plasmodium yoelii (Wikenheiser et al, 2018). Genetic disruption of the IL-21/IL-21R singling axis compromised P. chabaudi -specific IgG responses and resulted in the impairment of memory B cell generation.…”
Section: Protozoan Parasitesmentioning
confidence: 99%
“…72 These cells may also be important in modulating functional T follicular helper (Tfh) cell and germinal centre B-cell responses. 74 In contrast to these indirect roles in protection, cd T cells appear to act as important effector cells following vaccination with nonlethal Plasmodium yoelii sporozoites. 75 Results from mice lacking ab T cells further suggest that cd T-cell cytotoxicity may become more effective after interaction with CD4 + T cells.…”
Section: Malaria Infectionmentioning
confidence: 99%